2020
DOI: 10.1007/s11205-020-02518-1
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Family Resilience: Effects of Sustainable Livelihoods in Rural China

Abstract: Family resilience is the capacity of a family to mitigate adversity using its resources, structure, and internal connections. In rural China, where sustainable livelihoods are changing rapidly because of urbanization and migration, it is not clear how family resilience interacts with sustainability of livelihoods. This study of rural Chinese families classifies individual’s perceived family resilience and discusses how sustainable livelihoods influence this classification. A multilevel survey of rural families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Those components were also congruent with components of the organizational pattern by Walsh (2003). In addition, research done by Yang, Feldman, Li (2021) found that people from cooperative families can acquire family resilience by frequent cooperation. The organizational pattern consists of three subcomponents: flexibility, connectedness, & social and economic resources.…”
Section: Discussionsupporting
confidence: 53%
“…Those components were also congruent with components of the organizational pattern by Walsh (2003). In addition, research done by Yang, Feldman, Li (2021) found that people from cooperative families can acquire family resilience by frequent cooperation. The organizational pattern consists of three subcomponents: flexibility, connectedness, & social and economic resources.…”
Section: Discussionsupporting
confidence: 53%
“…Families have large social networks, and the more resources to which they have access, the stronger their resilience and the more easily they can adjust the family model and division of labor flexibly to suit the situation and allow the family to adapt to adversity ( 39 ). In the current situation of three-generation families in China, the supportive dual nurturing-feedback model dynamically shifts the focus of the family intergenerational relationship structure in a timely manner, which can help families cope with the dilemmas involved in care ( 39 ). Specifically, family resilience can be enhanced by changing roles within the family, altering lifestyles, adjusting needs and enhancing family care abilities ( 31 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Capital was decomposed into financial capital, human capital, social capital, physical capital, and natural capital. This type of livelihood construction focuses more on the material value of capital [ 3 , 35 ], arguing that livelihood strategies and levels of well-being are heavily influenced by various levels of and access to livelihood capital [ 1 , 36 ]. Among them, for rural residents, social capital is more effective in coping with external changes in rural network relations [ 37 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As urbanization continues to soar in China, urban and rural areas have taken different development paths in terms of economic structures and social networks, and therefore, urban and rural residents in China also have differing access to livelihoods [ 3 ]. While urban residents mostly rely on a combination of business, social security, and urban public services, which have high stability and sustainability, rural residents tend to sustain their livelihoods by using natural endowments, fixed assets, and social network resources [ 3 , 4 ]. Compared to rural residents, urban residents have higher levels of livelihood and better livelihood security [ 5 ].…”
Section: Introductionmentioning
confidence: 99%